Forced labour in the National Organisation „Service to Poland” 1948–1955. Between the rebellion and the capitulation - Jolanta Lenart (Edukacja Ustawiczna Dorosłych)
The100th anniversary of Poland regaining independence encourages us to reflect on its difficult road to obtaining actual freedom. It obliges us to recall events and attitudes not only of well-known heroes of past times, but also ordinary people who guided by wisdom, courage, and responsibility defended centuries-old Polish values. In the article, I am looking for the answers to the following questions: Can any constructive values be found in forced labour and what are they? What work attitudes were shaped by forced labour? I have based my reflections on the labour brigades of the "Service to Poland,” which was a labour organisation for the young created by communist authorities in 1948. Their official goal was to shape young people’s attitudes towards work, vocational training, and reconstruction of the country. The hidden goal, however, was the communist indoctrination of young people aiming at making them the so-called new people – "homo sovieticus", i.e. the obedient citizens of the new socialist state.